Physicochemical Characteristics of Pennar River, A Fresh Water Wetland in Kerala, India - P. V. Joseph; Claramma Jacob (E-Journal of Chemistry)
Some physicochemical characteristics of a fresh water wetland were investigated. The analysis was carried out for a period of two years. Physical parameters such as colour, odour, temperature, electrical conductivity (EC) total suspended solids (TSS) total dissolved substances (TDS), total solids (TS), turbidity and chemical parameters such as pH, alkalinity, hardness, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), chloride, salinity, flouride, phosphate & nitrate were examined. Results of the study indicated that water in Pennar river is highly contaminated and not safe for drinking. Uncontrolled use of chemical fertilizers and pesticides, unscrupulous dumping of domestic wastes are the major causes of deterioration of water. Poor quality of drinking water was recorded as the major risk factor for the large-scale water-borne diseases in the area.